RETRACTION NOTICE TO "Development and Validation of a Scale to Measure Academic Resilience of Students" - Honra, Joelash R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This article entitled “Development and Validation of a Scale to Measure Academic Resilience of Students” (2024), authored by Joelash R. Honra, published in Vol. 5, No. 1 of International Journal of Multidisciplinary: Applied Business and Education Research. 5(1), 140 – 149 has beenretracted as requested by the authors.